The Body Speaks: Using the Mirror Game to Link Attachment and Non-verbal Behavior - Feniger-Schaal, Rinat; Hart, Yuval; Lotan, Nava; Koren-Karie, Nina; Noy, Lior (Frontiers in Psychology, 2018)
The Mirror Game (MG) is a common exercise in dance/movement therapy and drama therapy. It is used to promote participants’ ability to enter and remain in a state of togetherness. In spite of the wide use of the MG by practitioners, it is only recently that scientists begun to use the MG in research, examining its correlates, validity and reliability. This study joins this effort by reporting on the identification of scale items to describe the nonverbal behaviour expressed during the MG and its correlation to measures of attachment. Thus, we explored the application of the MG as a tool for assessing the embodiment of attachment in adulthood. Forty-eight participants (22 females, mean age = 33.2) played the MG with the same gender-matched expert players. All MG were videotaped. In addition, participants were evaluated on two central measurements of attachment in adulthood: The Adult Attachment Interview (AAI) and the Experience in Close Relationship questionnaire (ECR). To analyse the data, we developed the “mirror game scale” that coded the nonverbal behavior during the movement interaction, using 19 parameters. The sub-scales were reduced using factor analysis into two dimensions referred to as “together” and “free”. The free factor was significantly correlated to both measurements of attachment: Participants classified as having secure attachment on the AAI, received higher scores on the MG free factor than participants classified as insecure (t (46) = 7.858, p =.000). Participants who were high on the avoidance dimension on the ECR, were low on the MG free factor (r (48) =-.-285, p = .007). This is the first study to examine the MG as it is used by practitioners and its correlation to highly standardized measures. This exploratory study may be considered as part of the first steps of exploring the MG as a standardized assessment tool. The advantages of the MG as a simple, non-verbal movement interaction demonstrate some of the strengths of dance/movement and drama therapy practice.